2007
DOI: 10.1111/j.1365-2214.2007.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of parents' approaches to health promotion in families of adolescents with physical disabilities

Abstract: Parents recognize that their child with a physical disability faces greater obstacles, and work hard at health promotion. Healthcare workers need to work with parents to: (1) provide information about specific lifestyle health behaviours including nutrition, physical activity and sexuality; (2) advocate for resources to foster social inclusion; and (3) discuss family strategies that balance parental involvement with their child's need for independence and energy conservation for daily activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 33 publications
2
43
0
2
Order By: Relevance
“…To ameliorate these adverse outcomes, periodic health and developmental screening, referral for specialty care, and anticipatory guidance around health promotion have been recommended (American Academy of Pediatrics Medical Home Initiatives for Children With Special Needs Project Advisory Committee, 2002). Previous evidence has suggested that such practices have not been implemented optimally (American Academy of Pediatrics Council on Children with Disabilities, Section on Developmental and Behavioral Pediatrics, Bright Futures Steering Committee, Medical Home Initiative for Children with Special Health Care Needs Project Advisory Committee, 2006), which could tax parents' time and emotional resources (Antle et al, 2007;Gould, 2003;Murphy et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…To ameliorate these adverse outcomes, periodic health and developmental screening, referral for specialty care, and anticipatory guidance around health promotion have been recommended (American Academy of Pediatrics Medical Home Initiatives for Children With Special Needs Project Advisory Committee, 2002). Previous evidence has suggested that such practices have not been implemented optimally (American Academy of Pediatrics Council on Children with Disabilities, Section on Developmental and Behavioral Pediatrics, Bright Futures Steering Committee, Medical Home Initiative for Children with Special Health Care Needs Project Advisory Committee, 2006), which could tax parents' time and emotional resources (Antle et al, 2007;Gould, 2003;Murphy et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Almost all parents enrolled their adolescent in recreational activities, often those especially for young people with disabilities. 41 Transportation to accommodate a wheelchair, attending the activity to assist their child, instruction of others on accommodations, and activity modifications are resources family members may need to enable their children's participation when they require physical assistance for mobility and self-care.…”
Section: Discussionmentioning
confidence: 99%
“…9 Other studies described that poor parent-child communication increased the risk of psychosocial problems in school-aged children. 21 Others recommended that the speech therapy aims at improving communication. A child need help to overcome a slight articulation problem, or she may not be able to communicate verbally and may require a non-verbal communication system.…”
Section: Resultsmentioning
confidence: 99%